Investigating the Effect of English Language Proficiency on Pragmatic Production of Apology by Jordanian EFL Learners - Al-Harbi, Hamzeh Mohammad; Suleiman, Raja Rozina Raja (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Communicating successfully in a language requires a good understanding of both linguistic and sociolinguistic aspects of that language. This understanding helps a speaker to use the right language in the right context for the right purpose. In such a case, the speaker can be referred to as communicatively competent. Communicative competence, which is considered an essential factor in achieving effective communicative goals (Bachman, 1990), is closely dependent on knowledge in both areas of grammar and pragmatics (Bardovi-Harlig & Dörnyei, 1998). However, communication breakdown can occur when non-native speakers (NNSs) lack either grammatical or pragmatic knowledge. Cohen (1996) argues that the “control of the vocabulary and grammar of the language without achieving a comparable control over the pragmatic or functional uses of the language” certainly leads NNSs to miscommunication (p. 253).